Haji Abdul Malik Karim Amrullah thoughts about inter-religious tolerance - Farhan Erlangga Ramadhan; M Japar; Achmad Husen (Universitas Ahmad Dahlan, 2021)
This study aims to analyze of Hamka's thoughts about inter-religious tolerance and its relevance to clause 29 verse (2) of the 1945 Constitution. The research used in this study is a qualitative descriptive method with the type of literature study. Data sources use primary data sources and secondary data sources. The data calibration technique in this research uses data triangulation and expert opinion. The data analysis technique uses reduction, data presentation, and conclusion. The results of the study show that in Hamka's thoughts about inter-religious tolerance, it can be seen using the conception in understanding tolerance according to Rainer Forst, including: (1) Tolerance as an attitude of mutual respect includes no compulsion on someone in embracing religion; and not tarnish the purity of other religions. (2) Tolerance as an attitude of mutual esteem includes doing justice and being kind; equality of human rights; tolerance. In addition, its relevance to clause 29 verse (2) of the 1945 Constitution lies in the use of the concept of tolerance, such as equality of human rights, no compulsion on a person to embrace religion, justice, and tolerance as an instrument that can be used by the state to provide protection and guarantees for the people in the freedom to embrace religion and worship according to their beliefs. The conclusion from this research is Hamka's thoughts about inter-religious tolerance are only limited to social interactions such as in social and humanitarian activities.